Experience-sharing Workshop in the co-development of NFWWCS in Eastern African Countries - Auma, Joseph; Amha, Yosef; Demissie, Teferi Dejene; Radeny, Maren A.O.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Many African countries are signatories to the Global Framework for Climate Services (GFCS) to support the development and use of climate information services (CIS) as a means to reduce the impacts of disasters from hydro-meteorological hazards and to effectively capacitate their communities to adapt to vagaries of climate variability and the ever-looming negative impacts of climate change. The effective and sustained delivery of CIS per this framework is vital to achieving, among others, the Paris Agreement’s adaptation goal of ‘enhancing adaptive capacity, strengthening resilience and reducing vulnerability to climate change (UNFCCC, 2015: Art. 7). The framework may also unlock funding support from international development and cooperation partners, with supports from United Nations System under the coordination of the World Meteorological Organization (WMO).